Plio-Pleistocene Plant Megafossils from the Lukundol Formation (Nakkhu Khola, Lalitpur District, Central Nepal)-First Results - Paudayal, Khum N. (Journal of Institute of Science and Technology, 2015)
The lacustrine sediments of the Kathmandu Basin are rich in plant mega and micro fossils. The Lukundol Formation which is distributed in the southern part of the Kathmandu Basin yielded nicely preserved plant megafossils from different locations. A 5.5 m thick carbonaceous clay bed at the left bank of the Nakkhu Khola, near Chyasikot village, Lalitpur contains abundant plant debris, leaf impressions, seed and fruits, gymnosperm needles and cones. The plant fossils discovered from this location are identified as Berberis asiatica (leaf), Rhododendron arboreum (leaf), Rhododendron barbatum (leaf), Litsea elongata (leaf), Pinus roxburghii (needles and cones) Trapa bispinosa and Trapa quadrispinosa (fruits). Many leaf impressions are also collected from Bungmati and Chovar area. This paper deals with the first reporting of plant fossils from Nakkhu Khola section. The findings from other sections will be reported separately. Journal of Institute of Science and Technology, 2015, 20(1): 141-144